Urinothorax - an uncommon complication following renal transplantation: a case report - Ferreira,Joel (2016)
Urinothorax is an uncommon cause of pleural effusion, mostly related to urinary tract injury or obstructive uropathy. Several pathophysiological mechanisms have been proposed to explain the transdiaphragmatic evasion of urine from an intra-abdominal collection known as urinoma. Biochemical analysis of pleural fluid and imagiological studies are essential for diagnosis, which requires a high index of suspicion. Treatment directed to the underlying cause and aimed at reducing intra-urinary pressure is sufficient in most cases. We report herein the case of a urinothorax in a young kidney transplant recipient. An early urinary leak occurred through an infarction area of the kidney graft. Successful conservative treatment involved thoracocentesis and prolonged double-J stenting and Foley catheterization